Study of Baryon Spectroscopy Using a New Potential Form - L. I. Abou-Salem (Advances in High Energy Physics)
In the present work, the nonrelativistic quark model is applied to study baryon systems, where the constituent quarks are bound by a suitable hyper central potential. We proposed a new phenomenological form of the interaction potential, digamma-type potential. Using the Jacobi coordinates, the three-body wave equation is solved numerically to calculate the resonance states of the N, Δ, Λ, and Σ baryon systems. The present model contains only two adjustable parameters in addition to the quark masses. Our theoretical calculations are compared to the available experimental data and Cornell potential results. The description of the spectrum shows that the ground states of the considered light and strange baryon spectra are in general well reproduced.